Site‐specific T–DNA integration in Arabidopsis thaliana mediated by the combined action of CRE recombinase and ϕC31 integrase. (15th May 2013) - De, Annelies; De, Sylvie; Nolf, Jonah; Van, Els; Depicker, Ann
Summary Random T–DNA integration into the plant host genome can be problematic for a variety of reasons, including potentially variable transgene expression as a result of different integration positions and multiple T–DNA copies, the risk of mutating the host genome and the difficulty of stacking well‐defined traits. Therefore, recombination systems have been proposed to integrate the T–DNA at a pre‐selected site in the host genome. Here, we demonstrate the capacity of the ϕC31 integrase (INT) for efficient targeted T–DNA integration. Moreover, we show that the iterative site‐specific integration system (ISSI), which combines the activities of the CRE recombinase and INT, enables the targeting of genes to a pre‐selected site with the concomitant removal of the resident selectable marker. To begin, plants expressing both the CRE and INT recombinase and containing the target attP site were constructed. These plants were supertransformed with a T–DNA vector harboring the loxP site, the attB sites, a selectable marker and an expression cassette encoding a reporter protein. Three out of the 35 transformants obtained (9%) showed transgenerational site‐specific integration (SSI) of this T–DNA and removal of the resident selectable marker, as demonstrated by PCR, Southern blot and segregation analysis. In conclusion, our results show the applicability of the ISSI system for precise and targeted Agrobacterium‐mediated integration, allowing the serial integration of transgenic DNA sequences in plants.